2016
DOI: 10.1007/s00125-016-3988-2
|View full text |Cite
|
Sign up to set email alerts
|

Family history of myocardial infarction, stroke and diabetes and cardiometabolic markers in children

Abstract: Aims/hypothesis Despite the overlap in occurrence of cardiovascular disease (CVD) and type 2 diabetes and their risk factors, family history of these diseases has not yet been investigated simultaneously in relation to cardiometabolic markers in offspring. We examined how a family history of CVD and/or diabetes relates to cardiometabolic markers in offspring, and to what extent these diseases independently contribute to cardiometabolic markers. Methods We used data from 1,374 12-year-old children and their par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…In concordance with our study, a cross sectional national survey in Sri Lanka ( n = 4485) demonstrated that family history of diabetes was associated with the prevalence of adults obesity as defined with the use of BMI [10]. Likewise, the Avon longitudinal study of parents and children (ALSPAC) ( n = 12,076) revealed that the grandchildren of maternal grandparents with DM were more likely to have higher birth weight than those grandchildren of non-grandparental diabetics [12], and a recent study in Netherlands indicated that children with strong family history of diabetes had higher total cholesterol [20]. In contrast, no association was observed between metabolic syndrome including obesity, insulin resistance, and glucose intolerance in F0 mice and obesity in grand-offspring (F2) by using a mouse model [21].…”
Section: Discussionmentioning
confidence: 99%
“…In concordance with our study, a cross sectional national survey in Sri Lanka ( n = 4485) demonstrated that family history of diabetes was associated with the prevalence of adults obesity as defined with the use of BMI [10]. Likewise, the Avon longitudinal study of parents and children (ALSPAC) ( n = 12,076) revealed that the grandchildren of maternal grandparents with DM were more likely to have higher birth weight than those grandchildren of non-grandparental diabetics [12], and a recent study in Netherlands indicated that children with strong family history of diabetes had higher total cholesterol [20]. In contrast, no association was observed between metabolic syndrome including obesity, insulin resistance, and glucose intolerance in F0 mice and obesity in grand-offspring (F2) by using a mouse model [21].…”
Section: Discussionmentioning
confidence: 99%
“…This site was chosen since the SA population comprises 27.7% of the local population and experiences a high T2DM disease burden (Desai et al, 2021) . Classification of family history was based on participants having at least one biological parent and grandparent diagnosed with T2DM (Berentzen et al, 2016). Staff at the collaborating clinic presented parents and/or grandparents with T2DM with the opportunity to enrol their children/grandchildren in SAADAP.…”
Section: Recruitment and Selection Criteriamentioning
confidence: 99%
“…In addition, cardio‐metabolic risk factors, such as increased blood pressure and lipid levels, visceral adiposity, insulin resistance, impaired glucose tolerance, and their combination, known as metabolic syndrome, are strong predictors for CVD risk in the general population and in people with T1D . Based on these data, the investigation of specific cardio‐metabolic risk factors and their clustering within families has become an appealing research area over the last years.…”
Section: Introductionmentioning
confidence: 99%
“…Based on these data, the investigation of specific cardio‐metabolic risk factors and their clustering within families has become an appealing research area over the last years. A recent study on a large population of 12‐year‐old children and their parents showed that a family history of CVD had a key impact on the cardio‐metabolic profile of the offspring, thus highlighting the importance of identifying CVD risk factors within families for preventive strategies . In adults with T1D a family history of hypertension or insulin resistance/type 2 diabetes has been associated with risk of DN in the offspring .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation